The Economic Effects of Brexit - Evidence from the Stock Market - Holger Breinlich; Elsa Leromain; Dennis Novy; Thomas Sampson; Ahmed Usman (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study stock market reactions to the Brexit referendum on 23 June 2016 in order to assess investors' expectations about the effects of leaving the European Union on the UK economy. Our results suggest that initial stock price movements were driven by fears of a cyclical downturn and by the sterling depreciation following the referendum. We also find tentative evidence that market reactions to two subsequent speeches by Theresa May (her Conservative Party conference and Lancaster House speeches) were more closely correlated with potential changes to tariffs and non-tariff barriers on UK-EU trade, indicating that investors may have updated their expectations in light of the possibility of a `hard Brexit'. We do not find a correlation between the share of EU migrants in different industries and stock market returns.
Keywords: F15; F23; G14; 330; Brexit; depreciation; event study; recession; stock market; tariffs